2021
DOI: 10.3390/ijms22105192
|View full text |Cite
|
Sign up to set email alerts
|

Sera from Patients with NMOSD Reduce the Differentiation Capacity of Precursor Cells in the Central Nervous System

Abstract: Introduction: AQP4 (aquaporin-4)–immunoglobulin G (IgG)-mediated neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory demyelinating disease that affects the central nervous system, particularly the spinal cord and optic nerve; remyelination capacity in neuromyelitis optica is yet to be determined, as is the role of AQP4–IgG in cell differentiation. Material and Methods: We included three groups—a group of patients with AQP4–IgG-positive neuromyelitis optica, a healthy group, and a sham group. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“… 48 Sera from NMO patients can enhance the production by SVZ neurospheres of GFAP + cells but reduce that of Tuj1 + (neurons) and Olig2 + (oligodendrocyte precursor cell). 37 Similarly, we found that NMO-IgG activates the proliferation of sub-ventricular cells and of qNSCs. NMO-IgG might have an effect not only directly on NSCs but also indirectly on targeting ependymocytes and astrocytes, leading to the release of inflammatory cytokines or transcription factors.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“… 48 Sera from NMO patients can enhance the production by SVZ neurospheres of GFAP + cells but reduce that of Tuj1 + (neurons) and Olig2 + (oligodendrocyte precursor cell). 37 Similarly, we found that NMO-IgG activates the proliferation of sub-ventricular cells and of qNSCs. NMO-IgG might have an effect not only directly on NSCs but also indirectly on targeting ependymocytes and astrocytes, leading to the release of inflammatory cytokines or transcription factors.…”
Section: Discussionsupporting
confidence: 61%
“… 16 , 17 However, the response of SV-NSCs is still unclear in NMO models. 37 Here, we evaluated the effects of NMO-IgG treatment during 24 hours on whole mount explant cultures. In the ependymal layer, quiescent neural stem cells (qNSCs) called B1 cells are able to produce precursors for neuroblasts and glial cells and project one process harbouring a single sensory cilium that is easily identified at the centre of ependymal surrounding pinwheels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is a need for future studies addressing two main issues: firstly, whether these cells remain resident and in a quiescent state in OPC niches, their survival times and the factors involved in their survival, and the potential role of OPC-loaded microparticles; and secondly, the capacity of HOG cells to respond to such demyelinating diseases as multiple sclerosis [ 31 ] and neuromyelitis optica [ 84 ], degenerative diseases such as Alzheimer disease [ 85 ], trauma [ 86 ], vascular diseases, and primary diseases of myelin, such as Alexander disease [ 87 ]. Although the implanted HOG cells can proliferate and differentiate in vitro, questions remain on whether they behave similarly in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Because demyelination severely impacts axonal and neuronal functions (Liu et al, 2018; Papadopoulos & Verkman, 2012), remyelination has been suggested as a potential therapeutic target for NMOSD since remyelination can, in principle, rescue the functions in the injured areas of the CNS (Tradtrantip et al, 2020; Yao et al, 2016). However, several mechanisms may induce limited remyelination in NMOSD model that include inhibition of oligodendrocyte progenitor cell (OPC) differentiation into mature oligodendrocytes (OLs), inhibiting OPC migration through damaged BBB, changes in microglia that limit phagocytosis of myelin debris, or axonal alterations (Gómez‐Pinedo et al, 2021). Astrocyte play a significant role in trophic support to neuronal and glial cells, and alterations in astrocytes metabolism induce pathological conditions that lead to oligodendrocyte cell death and demyelination (Matute et al, 2007).…”
Section: Introductionmentioning
confidence: 99%